ANALISIS LATIHAN PLYOMETRIC SEBAGAI METODE PENINGKATAN KECEPATAN DAN KELINCAHAN PEMAIN SEPAK BOLA DI DESA TAMAN FAJAR - Rahmat Syaifudin; Nanda Dwicahya; Misrodin (EDU RESEARCH, 2024)
Plyometric training is a method that is often used in developing the speed and agility of soccer players. This study aims to analyze the effectiveness of plyometric training in increasing the speed and agility of soccer players in Taman Fajar Village, Purbolinggo District, East Lampung Regency. The research method used was experimental with a quantitative approach, involving amateur soccer players who were divided into control and treatment groups. Measurements were taken before and after the training program using the 20-meter sprint test for speed and the Illinois Agility Test for agility. The results showed that the group undergoing plyometric training experienced significant improvements in speed and agility compared to the control group (p < 0.05). Plyometric training is proven to be effective in improving the physical performance of soccer players, especially in the aspects of explosivity and movement reaction. Thus, this method can be recommended as part of a routine training program for soccer players at both amateur and professional levels.